PENEGAKAN HUKUM DALAM PERTANGGUNG JAWABAN PIDANA TERHADAP PENERBIT IKLAN YANG MENYESATKAN DI WILAYAH HUKUM PENGADILAN NEGERI SAMARINDA - Nur Indah Sari (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
AbstrackIt is important to note the general publications both through advertisements and other media. Advertising as a means of communication and marketing plays an important role in society. Various ways can be taken so that manufacturers sell their products and services to consumers. Promotion form of advertising as a way for manufacturers, and with the advance of technology and supported by the emergence of private television stations and print media (magazines, newspapers, tabloids, brochures) that provides an alternative for manufacturers to introduce their products. The role of promotion in marketing management is not to under-emphasized again, both are indeed persuasive or informative.